2022
DOI: 10.1097/rlu.0000000000004009
|View full text |Cite
|
Sign up to set email alerts
|

Visual Assessment of 18F-FDG Uptake on PET to Predict Survival Benefit to PD-1 Blockade in Non–Small Cell Lung Cancer

Abstract: Background: Programmed death 1 (PD-1) blockade is a standard treatment for patients with metastatic non-small cell lung cancer (NSCLC). Approximately 20% patients receiving PD-1 blockade monotherapy can survive for more than 5 years. However, there are limited data on the optimal biomarkers for predicting long-term outcomes. Therefore, this study aimed to evaluate the prognostic significance of 18 F-FDG uptake in patients with NSCLC responding to PD-1 blockade. Patients and Methods: Thirty-eight patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Although PD-1/PD-L1 blockade exhibits remarkable anticancer efficacy and safety, it is estimated that it benefits less than half of applicable cancer patients ( 8 10 ). To better predict response to PD-1/PD-L1 blockade and avoid the waste of medical resources, robust biomarkers have been developed using various strategies, including imaging omics ( 27 , 28 ) and patient derived biological materials ( 29 31 ). Furthermore, genomic based biomarkers, like Tumor Mutational Burden ( 32 ), Antigen Processing Machinery score ( 33 ), Tumor Immune Dysfunction and Exclusion score ( 34 ) and Gene Expression Profiles score ( 35 ) are reported as prediction biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Although PD-1/PD-L1 blockade exhibits remarkable anticancer efficacy and safety, it is estimated that it benefits less than half of applicable cancer patients ( 8 10 ). To better predict response to PD-1/PD-L1 blockade and avoid the waste of medical resources, robust biomarkers have been developed using various strategies, including imaging omics ( 27 , 28 ) and patient derived biological materials ( 29 31 ). Furthermore, genomic based biomarkers, like Tumor Mutational Burden ( 32 ), Antigen Processing Machinery score ( 33 ), Tumor Immune Dysfunction and Exclusion score ( 34 ) and Gene Expression Profiles score ( 35 ) are reported as prediction biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…SUV max , MTV, and TLG (= SUV mean × MTV) were calculated semi-automatically for each tumor using the SUV mean value obtained from the liver VOI plus 1.5 SD as the threshold value. Active sites other than tumors, such as the myocardium, gastrointestinal tract, kidney, and urinary tract, were manually excluded from the direction of a certi ed nuclear medicine physician [11,15,18].…”
Section: Pet Imaging and Data Analysismentioning
confidence: 99%
“…Nowadays, 2-Deoxy-2-[ uorine-18]-uoro-d-glucose ( 18 F-FDG) positron emission tomography (PET) imaging is widely used as a convenient modality to distinguish benign from malignant lesions. Recently, several researchers have reported that metabolic tumor activity on 18 F-FDG uptake can predict the outcome of ICIs treatment in patients with advanced NSCLC [6][7][8][9][10][11]. As indicators of glucose metabolism within tumor cells, maximum standardized uptake values (SUV max ), metabolic tumor volume (MTV), and total lesion glycolysis (TLG) on 18 F-FDG accumulation have been investigated to determine the potential of a signi cant predictor; however, the metabolic activity of MTV or TLG may be appropriate for therapeutic monitoring or outcome after immunotherapy administration based on previous clinical evidence [6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, a ve-point scale (5-PS) based on 18 F-FDG uptake was used for therapeutic monitoring of patients with malignant lymphoma and NSCLC [12,13]. The 5-PS score was de ned as follows:…”
Section: Pet Imaging and Data Analysismentioning
confidence: 99%